Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat Pada Kantor Badan Pertanahan Nasional Kabupaten Tana Toraja - Deddy Cathur Putra; Isak Pasulu; Dwibin Kannapadang (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
The main problem in this study is whether service quality affects people's satisfaction at the Tana Toraja BPN Office. The data collection method used in this research is library research and field research. The population in this study were all of the people served at the Tana Toraja BPN Office as many as 38,761 people while the sample in this study was 100 people. The analytical method used is simple linear regression, the results of the study state that service quality has a positive and significant effect on community satisfaction at the Tana Toraja BPN Office.